Discrimination Against Vulnerable Groups in Exercising Their Voting Rights Due to Systemic Flaws in the Macedonian Electoral Legislation - Ristic, Jelena (European Scientific Journal, ESJ, 2020)
Various credible reports show that the Republic of North Macedonia has achieved a good level of democracy in terms of election and voting. However, there are still areas where improvements can be done in order to strengthen the constitutional right to vote of various groups of citizens. These groups of citizens include certain vulnerable groups, such as persons placed in facilities for care of the elderly and public health facilities for the treatment of mental illness, who seem to be placed in a less favourable position compared to other citizens. In this sense, the paper has placed its focus on analysis of certain systemic flaws within the Electoral Code and the effect they have on the voters placed in facilities for care of the elderly and public health facilities for the treatment of mental illness, especially in terms of discrimination against these vulnerable groups. Finally, conclusions will be drawn in order to contribute to the improvement of the protection of the constitutional right to vote of these vulnerable groups.